Al-ʻUlūm al-Ṭabīʻiyyah bayn Ḍarūrat al-Taʼṣīl wa Taḥaddiyyāt al-ʻAwlamah - Ali Thahir Syarifuddin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2003)
There are at least four things that are described in this paper, such as: the concept of science in general and the natural sciences in particular; revitalization of the natural sciences, and the challenges of globalization around the natural sciences. At this time there is a tendency to separate the natural sciences from the theological aspect. This paper seeks to restore the science in its place.